Initial field observations on Qaanaaq ice cap, northwestern Greenland. Issue 66 (2014) - Sugiyama, Shin; Sakakibara, Daiki; Matsuno, Satoshi; Yamaguchi, Satoru; Matoba, Sumito; Aoki, Teruo
Abstract: To study the glaciological processes controlling the mass budget of Greenland's peripheral glaciers and ice caps, field measurements were carried out on Qaanaaq ice cap, a 20 km long ice cap in northwestern Greenland. In the summer of 2012, we measured surface melt rate, ice flow velocity and ice thickness along a survey route spanning the ice margin (200m a.s.l.) to the ice-cap summit (1110m a.s.l.). Melt rates in the ablation area were clearly influenced by dark materials covering the ice surface, where degree-day factors varied from 5.44 mm w.e. K –1 d –1 on a clean surface to 8.26 mm w.e. K –1 d –1 in the dark regions. Ice velocity showed diurnal variations, indicating the presence of surface-meltwater induced basal sliding. Mean ice thickness along the survey route was 120 m, with a maximum thickness of 165 m. Ice velocity and temperature fields were computed using a thermomechanically coupled numerical glacier model. Modelled ice temperature, obtained by imposing estimated annual mean air temperature as the surface boundary condition, was substantially lower than implied by the observed ice velocity. This result suggests that the ice dynamics and thermodynamics of the ice cap are significantly influenced by heat transfer from meltwater and changing ice geometry.